Life cycle analysis of a mega underwater concrete RC structure - Xiao, Chen (2012)
The environmental impacts of refrigerant, 1,1,1,2-Tetrafluoroethane (R-134a), which is a HFC refrigerant, are analyzed by using the Life Cycle Analysis methodology. The main environmental issues of refrigerants include ozone depletion and global warming. After the establishment of the Montreal Protocol, all the refrigerants responsible to ozone depletion such as CFCs and HCFCs, are phased or being phased out nowadays. The most promising refrigerant will be HFC refrigerants because they have zero ozone depletion potential (ODP); however they have relatively high global warming potential (GWP). The Eco-indicator 99 method which is damage oriented is adopted to evaluate the environmental impacts of R-134a from its three stages, namely the production stage, the operation stage and the disposal stage. The total equivalent warming impact (TEWI) concept which includes direct warming impact due to leakage of the refrigerant and the indirect warming impact due to the energy consumption of the refrigerant is used to evaluate the impact of R-134a on global warming. It is found that 86.8% of the total impact is from energy consumption (mostly electricity consumption) during the operation stage.